1980
DOI: 10.1080/03014468000004431
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent growth spurt among rural Indian boys in relation to their nutritional status in early childhood

Abstract: The growth pattern of 677 rural Hyderabad boys aged between 13 and 18 years was studied over a year (1977-78) to obtain annual increments. These boys had earlier been studied over a four-year period (1965-69). Height for age at 5 years in relation to Boston standards was used to classify these subjects into four nutritional categories. The group that had experienced severe growth retardation in early life achieved a peak height velocity (6.9 cm/yr) similar to that of British boys (7.3 cm/yr), though the event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 6 publications
1
26
0
2
Order By: Relevance
“…Colli (1985), por sua vez, observou que meninas de alto nível sócio-econômico de Santo André apresentaram menarca mais cedo quando comparadas com aquelas de menor nível da mesma localidade. Em geral, os resultados obtidos no Brasil estão de acordo com os evidenciados em estudos conduzidos em outros países, que indicam que déficits nutricionais podem causar atraso na maturação sexual e no crescimento físico (Galler et al, 1985;Satyanarayana & Nadamuni Naidu, 1979;Satyanarayana et al, 1980). Em 1989, o Instituto Nacional de Alimentação e Nutrição do Ministério da Saúde (Inan, 1990) realizou a Pesquisa Nacional sobre Saúde e Nutrição (PNSN), que baseou-se em uma amostragem estrato-randomizada de 62 mil pessoas de todas as regiões do país.…”
Section: Maturação Sexualunclassified
“…Colli (1985), por sua vez, observou que meninas de alto nível sócio-econômico de Santo André apresentaram menarca mais cedo quando comparadas com aquelas de menor nível da mesma localidade. Em geral, os resultados obtidos no Brasil estão de acordo com os evidenciados em estudos conduzidos em outros países, que indicam que déficits nutricionais podem causar atraso na maturação sexual e no crescimento físico (Galler et al, 1985;Satyanarayana & Nadamuni Naidu, 1979;Satyanarayana et al, 1980). Em 1989, o Instituto Nacional de Alimentação e Nutrição do Ministério da Saúde (Inan, 1990) realizou a Pesquisa Nacional sobre Saúde e Nutrição (PNSN), que baseou-se em uma amostragem estrato-randomizada de 62 mil pessoas de todas as regiões do país.…”
Section: Maturação Sexualunclassified
“…Among boys, the height increment from 5 ±18 y of age was only 1 cm higher for the boys with a preschool height-for-age below 74 than for those with a height-for-age above 72 (Satyanarayana et al, 1980). However, when the boys were followed until total arrest of growth, the height increment was 5.5 cm higher for the group of boys who were smallest at 5 y compared to the tallest (Satyanarayana et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Vijayaraghavan et al (1974) and Visweswara reported that the arm economic groups were considerably smaller than those of well to do children of corresponding ages. The effect of socio economic condition on growth pattern of Indian children also been revealed in other studies (Roa and Sastry, 1977;Satyanarayana et al, 1980;National Nutrition Monitoring Bureau 1980;Bharati and Basu 1990).…”
Section: Introductionmentioning
confidence: 83%